Energy Efficiency Barriers in Commercial and Industrial Firms in Ukraine : An Empirical Analysis - Hochman, Gal (Elsevier, 2018)
Improvement in energy efficiency is one of the main options to reduce energy demand and greenhouse gas emissions. However, large-scale deployment of energy-efficient technologies is constrained by several factors. Employing a survey of 509 industrial and commercial firms throughout Ukraine and a generalized ordered logit model, we quantified the economic, behavioral, and institutional barriers that may impede the deployment of energy-efficient technologies. Our analysis shows that behavioral barriers resulted from lack of information, knowledge, and awareness are major impediments to the adoption of energy-efficient technologies in Ukraine, and that financial barriers may further impede investments in these technologies especially for small firms. This suggests that carefully targeted information provisions and energy audits will enhance Ukrainian firms' investments in energy-efficient technologies to save energy consumption, improve productivity, and reduce carbon emissions from the productive sectors.